2010
DOI: 10.1111/j.1442-9993.2010.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Are the patterns of regeneration in the endangeredEucalyptus gunniissp.divaricatashifting in response to climate?

Abstract: Increasing drought frequency is a major driver of changes in forest structure and has been implicated in the decline of the endangered tree species, Eucalyptus gunnii ssp. divaricata (McAulay & Brett) in the Central Plateau region of Tasmania, Australia. In this study, we examined patterns of regeneration, aspects of the water relations of E. gunnii ssp. divaricata and its replacement Eucalyptus pauciflora and, whether shifts in stand dominance have occurred where the subspecies co‐occurs with E. pauciflor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…Other microsite studies (Lamont et al, 1993;Sanger et al, 2010) have concluded that the relative safeness of a seedling recruitment microsite depended on its effect on water availability. Our results support and expand on this principle, indicating that, seedling microsites within Tasmanian dry eucalypt forests are characterised by ashbeds with: soft soil that facilitates root growth and water capture; soil that is less water repellent than the general forest floor; low cover of grass (limiting competition between grass and eucalypt seedlings for soil water); charcoal with possible water retention and insulation properties and coarse woody debris that provides shelter and an adjacent reservoir of stored soil moisture.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other microsite studies (Lamont et al, 1993;Sanger et al, 2010) have concluded that the relative safeness of a seedling recruitment microsite depended on its effect on water availability. Our results support and expand on this principle, indicating that, seedling microsites within Tasmanian dry eucalypt forests are characterised by ashbeds with: soft soil that facilitates root growth and water capture; soil that is less water repellent than the general forest floor; low cover of grass (limiting competition between grass and eucalypt seedlings for soil water); charcoal with possible water retention and insulation properties and coarse woody debris that provides shelter and an adjacent reservoir of stored soil moisture.…”
Section: Resultsmentioning
confidence: 97%
“…These protected microsites were described as physical microhabitats, or ''protected sites created by, for example, stones, depressions or fallen logs'' (Potts, 1986). Sanger et al (2010), found that the regeneration of Eucalyptus gunnii ssp. divaricata, an endangered species from the relatively wet and cold Central Plateau of Tasmania, appeared to be shifting to microsites of increased water holding capacity in response to an observed 25% reduction in summer rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The climate is becoming hotter, with rainfall more seasonal and distinct dry periods (e.g. Sanger et al ). Eucalypt genetic research (Gauli ) has shown a strongly heritable variation in physiology and morphology in response to the maximum temperature of the warmest month.…”
Section: Outcomes and Challengesmentioning
confidence: 99%
“…For example, at the lowest elevation trial, survival diminished in the local E. gunnii provenance compared with a provenance originating from an even lower (warmer) elevation, but this trend did not become evident until 25 years after planting (Potts 1985;Figure 8). Maximum temperatures in the region of the field trial have increased by 0.21˚C per decade over the last 50 years and late summer/autumn rainfall has decreased by 25% (Sanger et al 2011), which may have contributed to the observed change in provenance performance. This shift coincides with extensive dieback in the local E. gunnii in this region and a shift in its regeneration niche to deeper soils (Calder & Kirkpatrick 2008;Sanger et al 2011).…”
Section: Plant Performancementioning
confidence: 99%
“…Maximum temperatures in the region of the field trial have increased by 0.21˚C per decade over the last 50 years and late summer/autumn rainfall has decreased by 25% (Sanger et al 2011), which may have contributed to the observed change in provenance performance. This shift coincides with extensive dieback in the local E. gunnii in this region and a shift in its regeneration niche to deeper soils (Calder & Kirkpatrick 2008;Sanger et al 2011). …”
Section: Plant Performancementioning
confidence: 99%